2020
DOI: 10.1007/s00256-020-03543-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying in vivo scaphoid, lunate, and capitate kinematics using four-dimensional computed tomography

Abstract: Objective We aimed to establish a quantitative description of motion patterns and establish test-retest reliability of the four-dimensional CT when quantifying in vivo kinematics of the scaphoid, lunate, and capitate. Materials and methods We assessed in vivo kinematics of both wrists of 20 healthy volunteers (11 men and 9 women) between the ages of 20 and 40 years. All volunteers performed active flexion-extension and radial-ulnar deviation with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…The preliminary dynamic profiles derived within this exploratory study are encouraging, Profiles derived from this study agree with the recent similar studies using dynamic 4D-CT imaging of healthy subjects. In particular, the present findings agree with those of Brinkhorst et al, [ 18 ], Foumani et al, [ 33 ] and of Crisco et al, [ 30 ]. In addition, the present results suggested that scaphoid and lunate rotate linearly with the wrist rotation during the flexion-extension motion, which agrees with results derived from recent cadaveric studies [ 34 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The preliminary dynamic profiles derived within this exploratory study are encouraging, Profiles derived from this study agree with the recent similar studies using dynamic 4D-CT imaging of healthy subjects. In particular, the present findings agree with those of Brinkhorst et al, [ 18 ], Foumani et al, [ 33 ] and of Crisco et al, [ 30 ]. In addition, the present results suggested that scaphoid and lunate rotate linearly with the wrist rotation during the flexion-extension motion, which agrees with results derived from recent cadaveric studies [ 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…To describe the rotational parameters of the scaphoid, lunate, and capitate bones, an anatomically-based coordinate system was referenced to the distal radius using anatomic features of the radial surface ( Fig 4 ). This radius coordinate system (RCS) is a modification of the International Society of Biomechanics (ISB) recommendation [ 27 ] and has been used in several recent dynamic studies of wrist carpal bones [ 18 , 28 30 ].…”
Section: Motion Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The normal motion of the pisotriquetral joint during wrist flexion/extension, with measurements of the anteroposterior interval and craniocaudal excursion, has also been described, with good interobserver agreement of the first measurement 31 . Recent quantification of scaphoid, lunate, and capitate motions in healthy individuals by using 4DCT have also been reported, with high test-retest reliability correlations 36 . Similar studies have also been conducted on varying wrist motions such as during radioulnar deviation, pronosupination 37 …”
Section: -Dimensional Ctmentioning
confidence: 88%
“…31 Recent quantification of scaphoid, lunate, and capitate motions in healthy individuals by using 4DCT have also been reported, with high test-retest reliability correlations. 36 Similar studies have also been conducted on varying wrist motions such as during radioulnar deviation, pronosupination. 37…”
Section: Wrist Imagingmentioning
confidence: 98%